2021
DOI: 10.3390/en14206824
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Review on Decision Approaches for Clean Energy Systems under Uncertainty

Abstract: This paper aims to provide a bibliometric review on the diverse decision approaches in uncertain contexts for clean energy system (CES) assessment. A total of 126 publications are analyzed. Previous reviews on CES have discussed several research questions on the decision methods and the applicability of evaluating CES, along with the factors associated with CESs. In the present study, we focus on the bibliometric aspect that attempts to address questions related to the prominence of authors, countries/regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…Karagöz 65 incorporated ARAS with “interval type-2 fuzzy sets (IT2FSs)” for the evaluation of recycling facility locations from SD context. Pandey et al 66 provide a review on decision methods under uncertainty for clean energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Karagöz 65 incorporated ARAS with “interval type-2 fuzzy sets (IT2FSs)” for the evaluation of recycling facility locations from SD context. Pandey et al 66 provide a review on decision methods under uncertainty for clean energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study system feeds the estimated demand of 7475 inhabitants of the island of San Cristóbal, in the Galapagos archipelago, whose consumption is estimated at 1.4 (kW.h -1 ) per family [15]. The proposed hybrid system is composed of a group of seven combustion generators with a total capacity of 9.8 MW, a group of three wind turbines with a total power of 2.4 MW, a photovoltaic system of 0.95 MW, a solar thermal eld with a capacity of 1 MW and a "Battery Energy Storage System (BESS)" of 6.5 MW [16].…”
Section: Case Studymentioning
confidence: 99%
“…The horizontal-axis WTs, on the other hand, can be either upwind or downwind, equipped with a yaw drive and motor to turn the nacelle windward. These turbines are typically either two-or three-bladed and are convention- Mathematical analyses of the suitability of different forms of clean and renewable energies were carried out in the recent past [35][36][37][38]. Based on review models related to decision approaches for clean energy systems, it was found that wind energy constituted of highest proportion due to convenience and availability.…”
Section: Introductionmentioning
confidence: 99%